The Australian Prisons Census: Estimating remand times - Collins, Mark F. (Journal of quantitative criminology, 1995)
By applying a renewal theory model to data from the Australian Prisons Census, we estimate the number of remand receptions at prisons and the mean and median remand times served by prisoners during the period 1982–1990. We conclude that despite the general increases in court delays, and despite a large increase in the remand reception rate between 1982 and 1990, remand times have been largely unaffected, with the median remand time for 1990 being 1.7 weeks. Comparisons are made with official figures for various states and with figures for Canada and England/Wales.